Finding Chika : a little girl, an earthquake, and the making of a family - Albom, Mitch (New York : Harper, 2019)
A memoir of a Haitian orphan named Chika, taken in by the author and his wife, exploring love, illness, and family.
Keywords: Adopted children -- Haiti -- Biography; Earthquake victims -- Haiti -- Biography